Fraternal twins: distinction between PbPc and SnPc by their switching behaviour in a scanning tunnelling microscope. (7th February 2019) - Forker, Roman; Gruenewald, Marco; Sojka, Falko; Peuker, Julia; Mueller, Philipp; Zwick, Christian; Huempfner, Tobias; Meissner, Matthias; Fritz, Torsten
Abstract: In this contribution, we compare the optical absorbance behaviour and the structural properties of lead(II)-phthalocyanine (PbPc) and tin(II)-phthalocyanine (SnPc) thin films. To this end, we employ a Ag(1 1 1) substrate terminated with a monolayer of 3, 4, 9, 10-perylene tetracarboxylic dianhydride constituting an internal interface whose main effect is an electronic decoupling of the phthalocyanine adlayer from the metal surface. As deduced from low-energy electron diffraction and scanning tunnelling microscopy (STM) measurements, the epitaxial relations and unit cell compositions of the prevailing PbPc monolayer and multilayer domains are confusingly similar to those of SnPc on PTCDA/Ag(1 1 1). However, SnPc and PbPc can be readily distinguished by their STM-induced switching behaviours: while the former is capable of reversible configurational changes, no effect on the latter could be achieved by us under comparable conditions. This corroborates earlier theoretical predictions and even renders the chemical identification of individual shuttlecock-shaped metal-phthalocyanines feasible.